Stock Information on Social Media and Stock Return - Zhulvira Syafitri; Ani Wilujeng Suryani (The Indonesian Journal of Accounting Research, 2022)
Information on social media, both positive and negative, can spread quickly so that it can affect the company's stock price. This study aims to determine the effect of posting on Instagram on abnormal returns. The sample used is 2,675 posts from 18 stock news accounts. Generalized Least Squares (GLS) regression is used to determine the impact of posting on Instagram on abnormal returns. The results showed that sentiment on social media had a positive effect on abnormal returns. However, there is a possibility of misinterpretation by investors and the participation of impostors, so the impact of information on social media on abnormal returns is only temporary. This study contributes to the behavioral finance literature by examining the effect of sentiment on Instagram on abnormal returns. In addition, information on social media can be utilized by investors by selling their ownership when the stock gets positive sentiment to get abnormal returns. Investors can buy stocks when there is a negative sentiment on social media because the stock price is lower than its intrinsic value, so it has the potential to increase again.